이연법인세자산의 인식과 이익조정 - 안숙찬(An, Sook-Chan) (대한경영학회지, 2007)
1998년 4월 1일에 도입된 이연법인세회계는 이연법인세자산의 인식과 관련하여 경영자의 재량권을 상당한 정도 허용하고 있기 때문에 경영자의 판단에 따라 이연법인세자산으로 계상되는 차감할 일시적차이에 대한 법인세효과의 크기가 상당히 달라질 수 있다. 본 연구는 우리나라 상장기업을 대상으로 기업이 이익조정목적으로 이연법인세자산을 회계처리하는지 실증분석 하였다. 1999년부터 2002년까지 이연법인세자산을 인식한 상장기업 625개 기업/연도를 대상으로 분할표를 이용한 분석과 로짓분석을 수행한 결과, 직전연도보다 이연법인세자산 인식률을 높인 기업들의 경우에 이익조정행위가 있었다는 증거를 발견하지는 못하였다. 그러나 이연법인세자산 인식률을 낮춘 기업의 경우에는 'big bath'를 형성하기 위한 이익조정행위가 있었던 것으로 나타났다. Korean accounting standards interpretation 45-52 'accounting for income taxes', which was first applied from the fiscal year starting from April 1998, allowed a considerable discretion of managers in recognizing the deferred tax assets. So, the amount of the deferred tax assets recorded in the financial statements could be adjusted by the mangers' own decisions. This study examined whether Korean firms accounted for the deferred tax on the purpose of managing earnings. The sample consisted of 625 publicly traded firms-years with December fiscal year-end over the period 1999-2002, and test and logistic regression analysis were used. The empirical results showed that the firms that increased their recognition rates of the deferred tax assets seemed not to manage earnings in recognizing the deferred tax assets. However, the firms that decreased their recognition rates of the deferred tax assets might mange earnings for invoking an earnings 'big bath'. KCI Citation Count: 9